Revisão da Medicação em Idosos Institucionalizados: Aplicação dos Critérios STOPP e START - Catarina Metelo de Nápoles Periquito; Patrícia Cavaco Silva; Pedro Oliveira; Clara Carneiro; Ana Isabel Fernandes; Filipa Alves da Costa (Formifarma, LDA., 2014)
Introduction: Elderly population is frequently polymedicated, including with potentially inappropriate medications (PIM), sometimes instead of preventive medication, designated as potentially prescribing omissions (POM). Objectives: This study aims to characterize and to quantify the occurrence of PIM and POM in a sample of institutionalized elderly patients through a medication review using STOPP (Screening Tool of Older Person's Prescriptions) and START (Screening Tool to Alert doctors to Right Treatment) criteria. Methods: A descriptive cross-sectional study was used, where 4 elderly facilities were invited to participate. Patients aged ≥65 and using ≥5 medicines were included in the study and their medication was analyzed using STOPP and START criteria. Data were analyzed using univariate and bivariate descriptive statistics (Mann-Whitney U and Kruskal-Wallis tests), considering a significance level of 95%. Results: The final sample included 126 individuals, with a mean age of 84.81 years (SD=6.126), 69.0% being female. A total of 1315 medicines were analyzed, and 214 PIM (16.27%) and 90 POM (6.84%) were identified through the application of the STOPP and START criteria, respectively. Data indicates that 75.4% of the sample had one or more PIM (M=1.71 /patient; SD=1,470) and 42.9% had one or more POM (M=0.72/patient; SD=1,048). Conclusion: The application of the STOPP and START criteria enabled the identification of a considerable amount of PIM and POM, indicating them as tools that contribute to review and change, if necessary, the instituted therapy in elderly. The development of pharmaceutical competencies in the care of geriatric patients, even though not evaluated in the current study, may constitute the basis for future opportunities for pharmaceutical intervention and valuing of the pharmacist's role.